Microchoerus hookeri nov. sp., a new late Eocene European microchoerine (Omomyidae, Primates): New insights on the evolution of the genus Microchoerus. Issue 102 (January 2017) - Minwer-Barakat, Raef; Marigó, Judit; Femenias-Gual, Joan; Costeur, Loïc; De Esteban-Trivigno, Soledad; Moyà-Solà, Salvador
Abstract: The study of Eocene primates is crucial for understanding the evolutionary steps undergone by the earliest members of our lineage and the relationships between extinct and extant taxa. Recently, the description of new material from Spain has improved knowledge of European Paleogene primates considerably, particularly regarding microchoerines. Here we describe the remains of Microchoerus from Sossís (late Eocene, Northern Spain), consisting of more than 120 specimens and representing the richest sample of Microchoerus from Spain. This primate was first documented in Sossís during the 1960s, on the basis of scarce specimens that were ascribed to Microchoerus erinaceus . However, the studied material clearly differs from M. erinaceus at its type locality, Hordle Cliff, and shows some characters that allow the erection of a new species, Microchoerus hookeri . This new species is characterized by its medium size, moderate enamel wrinkling, generally absent mesoconid and small hypoconulid in the M1 and M2, single paracone in the upper molars and premolars and, particularly, by the lack of mesostyle in most M 1 and M 2, a trait not observed in any other species of Microchoerus . Some specimens from Eclépens B (late Eocene, Switzerland), determined previously to be Microcherus aff. erinaceus, are also ascribed to M. hookeri . M. hookeri represents the first step of a lineage that differentiated from Necrolemur antiquus and, later, gave rise to several unnamed forms of Microchoerus, such as those from Euzet and Perrière, finally leading to M. erinaceus . This discovery sheds new light on the complex evolutionary scheme of Microchoerus, indicating that it is most probably a paraphyletic group. A detailed revision of the age of the localities containing remains of Microchoerus and the description of the still unpublished material from some European localities, are necessary to clarify the phylogenetic relationships among the members of this microchoerine group.